2022
DOI: 10.1039/d1ob02331d
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in enantio- and diastereoselective hydrogenation of N-heteroaromatic compounds

Abstract: The enantioselective and diastereoselective hydrogenation of N-heteroaromatic compounds is an efficient strategy to access chirally enriched cyclic heterocycles, which often possess highly bio-active properties. This strategy, however, has only been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 174 publications
0
22
0
Order By: Relevance
“…Although catalytic hydrogenation with molecular hydrogen gas is a very atom-efficient strategy, high pressures and temperatures are generally required to break the aromaticity in the substrates. [11][12][13] Hence, specialized reaction equip-ment and safety procedures must be in place for handling and storing of the highly flammable hydrogen gas. As an alternative, catalytic transfer hydrogenation with H 2 -surrogates, such as isopropanol or formic acid, offers a mild yet powerful method due to its operational simplicity and the widespread availability of suitable reducing agents.…”
mentioning
confidence: 99%
“…Although catalytic hydrogenation with molecular hydrogen gas is a very atom-efficient strategy, high pressures and temperatures are generally required to break the aromaticity in the substrates. [11][12][13] Hence, specialized reaction equip-ment and safety procedures must be in place for handling and storing of the highly flammable hydrogen gas. As an alternative, catalytic transfer hydrogenation with H 2 -surrogates, such as isopropanol or formic acid, offers a mild yet powerful method due to its operational simplicity and the widespread availability of suitable reducing agents.…”
mentioning
confidence: 99%
“…[6][7][8] Indeed, heteroarene hydrogenation reactions are regularly employed to deliver medicinallyrelevant saturated or partially-saturated heterocyclic motifs from widely available heteroaromatic starting materials. [9][10][11] In principle, heteroarene hydrofunctionalization constitutes a deceptively simple class of complementary dearomatization reactions (Figure 1A). These transformations disrupt planarity while also installing a new molecular vector.…”
Section: Interrogation Of Increasingly Complex 3d Target Moleculesmentioning
confidence: 99%
“…We suspect this sharp sensitivity to the nitrogen protecting group may be a consequence of the highly polarized CO 2 *À nucleophile. However, the reaction is otherwise insensitive to indole electronics; substrates decorated with a variety of electron-donating and electronwithdrawing groups each underwent the desired transformation in high yields (5)(6)(7)(8)(9)(10)(11). These studies also revealed that dearomative hydrocarboxylation is favored over undesired side reactions at diverse medicinally relevant but potentially sensitive functional groups, such as carbamates (4, 11), aryl fluorides (5), thioethers (7), amides (9, 20), amines (10)(11), and pyridines (12-16, 18, 19).…”
Section: Interrogation Of Increasingly Complex 3d Target Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In the list of FDA-approved pharmaceuticals, piperazine is the third most prevalent saturated N-heterocycle. 27 On this point, we executed and optimized solvent-free mechanochemical procedures for obtaining a library of N-substituted amines under milder reaction conditions in a short reaction time with excellent yields without any further purification. The optimized protocol was also well demonstrated for other heteroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%